1988
DOI: 10.1139/m88-041
|View full text |Cite
|
Sign up to set email alerts
|

Purification of extracellular amylolytic enzymes from the thermophilic fungus Thermomyces lanuginosus

Abstract: When grown in static culture it appears as if Thermomyces lanuginosus has a biphasic secretion of the extracellular starch-degrading activity. This could be due to the presence of at least two different amylases. By ion-exchange chromatography on DEAE-Trisacryl an α-amylase (EC 3.2.1.1) and a glucoamylase (EC 3.2.1.3) were separated and purified from the extracellular protein from 14-day-old static cultures grown on soluble starch. The hydrolysis of soluble starch by the purified glucoamylase resulted in only … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

1991
1991
2021
2021

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(12 citation statements)
references
References 5 publications
0
11
0
1
Order By: Relevance
“…The glucoamylase from the thermophilic fungus Thermomyces lanuginosus is a candidate in this respect. Glucoamylase from this thermophile has been described by Taylor et al (1978) and Basaveswara Rag et al (1979Rag et al ( , 1981, Jensen et al (1988) showed that several extracellular amylolytic activities viz. alpha-amylase, glucoamyOffprint requests to: I. Haasum lase and alpha-glucosidase were excreted when T. lanuginosus was cultivated in agar-free YpSs medium (Emerson 1941).…”
Section: Introductionmentioning
confidence: 86%
See 4 more Smart Citations
“…The glucoamylase from the thermophilic fungus Thermomyces lanuginosus is a candidate in this respect. Glucoamylase from this thermophile has been described by Taylor et al (1978) and Basaveswara Rag et al (1979Rag et al ( , 1981, Jensen et al (1988) showed that several extracellular amylolytic activities viz. alpha-amylase, glucoamyOffprint requests to: I. Haasum lase and alpha-glucosidase were excreted when T. lanuginosus was cultivated in agar-free YpSs medium (Emerson 1941).…”
Section: Introductionmentioning
confidence: 86%
“…1457, The Royal Verterinary and Agricultural University, Copenhagen, Denmark). Conidiated cultures were produced as previously described (Jensen et al 1988) and maintained on YpSs agar (Emerson 1941) (Vogel 1964). In some of the experiments starch was replaced by maltose (5885, Sigma, St. Louis, Mo., USA) and yeast extract by one of eight nitrogen sources in concentrations equivalent to the amount of nitrogen in yeast extract.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations